Dynamics of Public Trust Toward BAZNAS Post-Corruption Allegations: A Qualitative Phenomenological Study of Muzakki with Digital Sentiment Analysis - Haryanti, Peni; Dwi Ari Pertiwi; Athi’ Hidayati (Balanca : Jurnal Ekonomi dan Bisnis Islam, 2026)
Public trust constitutes the fundamental capital in the management of national zakat institutions. However, a significant research gap exists in understanding the dynamics of trust reconstruction following institutional corruption scandals in Islamic philanthropic organizations, particularly studies that integrate phenomenological approaches with digital sentiment analysis. This study aims to analyze the dynamics of public trust toward the National Zakat Agency (BAZNAS) following corruption allegations, through the perspectives of muzakki and social media sentiment analysis. The study employed an interpretive qualitative design with a phenomenological approach (Colaizzi method) involving 15 purposively selected muzakki informants, complemented by content and sentiment analysis of 1,247 comments collected from Instagram, Twitter/X, Facebook, and YouTube during November 2024 through March 2025. Phenomenological analysis identified three essential experiential themes: spiritual-institutional shock (100%), compliance-trust dilemma (86.7%), and adaptive resistance (80.0%). Digital sentiment analysis corroborated a corresponding three-phase temporal pattern: (1) a denial-defensive phase (53.0% neutral sentiment); (2) an anger-disappointment phase (67.4% negative); and (3) an adaptive-constructive phase (22.1% positive). Triangulation between phenomenological findings and digital sentiment analysis demonstrated strong thematic alignment. This study contributes a novel phenomenologically-grounded framework that employs computational sentiment analysis as a triangulating instrument in the context of Islamic philanthropic trust management in Indonesia.